PATTERN OF BACTERIAL ISOLATES SUSCEPTIBILITY TO ANTIBIOTICS IN THE INTENSIVE CARE UNIT: A CROSS-SECTIONAL STUDY. - Rajan Pathak; Kumar, Mukesh; Ojha, Rakshita; Richa Singh; Sangwan, Jyoti (Student's Journal of Health Research Africa, 2023)
Background Infection control has been a major problem for the past two decades due to the rapid emergence of antimicrobial resistance (AMR). Most antibiotic resistance develops in intensive care units. Due to antimicrobial resistance management of infectious diseases becomes a challenge, and physicians need antibiograms with recent updates to develop a treatment plan for the patients. Aim To study the antibiogram of isolated bacterial culture from the intensive care unit. Materials and Methods A retrospective study was conducted from October 2021 to April 2023 . A total of 150 patients’ samples, received from various ICUs, were processed according to the standard protocol. Various specimen types were aseptically collected and sent to the NMCH Microbiology Laboratory. Antibiotic susceptibility tests followed the Kirby-Bauer disk diffusion method. Statistical analysis was performed using SPSS, with significance set at P<0.05. Results The study included patients aged 0 to 85 years, most admissions were in the Surgical ICU (47.1%), primarily with pus (30.6%) and blood samples (25.3%). Among 85 samples with bacterial growth, 56.66% were Gram-negative bacilli, with Pseudomonas spp. (15.69%) as the leading isolate. Gram-positive organisms (43.13%) included Methicillin-resistant Staphylococcus aureus (15.69%). Pseudomonas was highly sensitive to Colistin (100%) but resistant to Ceftazidime and Tetracycline. MRSA showed sensitivity to Vancomycin and Linezolid but resistance to Cefoxitin, Tetracycline, and Levofloxacin. Conclusion This study highlights the importance of antimicrobial resistance in intensive care units, where most antibiotic resistance arises. The prevalence of multidrug-resistant Gram-negative bacilli like Pseudomonas spp. and MRSA is alarming. Sensitivity patterns show standard antibiotics' low efficiency against certain bacteria. The findings highlight the need for updated and personalized antibiograms to guide ICU treatment methods, where AMR makes infectious illness management difficult. Recommendation Screening of the admitted patients can help generate the data and develop a plan which can effectively treat nosocomial infections.